2013
DOI: 10.5539/jas.v5n2p134
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and Crop Yields along the Terraces and Toposequece of Anjeni Watershed, Central Highlands of Ethiopia

Abstract: In the Highlands of Ethiopia, soil erosion is a pressing challenge causing deterioration of soil quality including soil fertility. To overcome this problem, the government has been taking various sustainable land management (SLM) measures. This study was conducted in 2011 to investigate the long-term impacts of soil conservation on soil qualities and crop performance at Anjeni watershed in the central highlands of Ethiopia. Soil and crop samples were collected from the lower (deposition), middle and upper (los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
67
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 24 publications
20
67
3
Order By: Relevance
“…This could be due to low soil organic carbon and high soil compaction by livestock grazing in non-conserved open communal grazing lands. The results of other studies also clearly showed the important role of organic matter for rehabilitating degraded soils by improving other soil properties [51,52]. The BD decreased 1.28-1.26 g cm −3 due to terrace Table 5 Effect of slope position on SOC concentration, SOC stock, and soil bulk density (Mean ± SEM)…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This could be due to low soil organic carbon and high soil compaction by livestock grazing in non-conserved open communal grazing lands. The results of other studies also clearly showed the important role of organic matter for rehabilitating degraded soils by improving other soil properties [51,52]. The BD decreased 1.28-1.26 g cm −3 due to terrace Table 5 Effect of slope position on SOC concentration, SOC stock, and soil bulk density (Mean ± SEM)…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Mekuria and Veldkamp [48] in northern highlands of Ethiopia and Amare et al [51] in Anjeni Watershed in central highlands of Ethiopia found higher SOC in lower and depositional zone than upper and loss zones.…”
Section: Swc Measures Mbc (Mg Kgmentioning
confidence: 74%
“…Terraces decreased surface erosion and improved soil conditions [4]. Soil quality was improved after installation terraces [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts towards integrated soil fertility management practices may help to improve crop productivity that may lead to sustainable agriculture. For example long term investment on soil and water conservation (SWC) in the highlands of Ethiopia improved soil fertility (Adgo et al, 2013;Alemu et al, 2013;Amare et al, 2013). Ethiopian farmers also use various cultural soil fertility improvement practices such as inter cropping, crop rotation, fallowing and farmyard manure.…”
Section: Introductionmentioning
confidence: 99%